Pengembangan Media Video Pembelajaran untuk Meningkatkan Pengembangan Storyboard Mata Kuliah Animasi 2 Dimensi dan 3 Dimensi - Ainur Rofik; Andi Mariono; Alim Sumarno; Ainur Rofik; Andi Mariono (Universitas Negeri Malang, 2025)
The aim of this research is to determine the improvement in students' skills in developing storyboards after the use of instructional video media in the 2D and 3D Animation course in the Bachelor’s Program of Educational Technology at UNESA. This study employs a quantitative approach. The data were collected from students' practical scores in storyboard creation. The sample consists of 39 students from the Educational Technology department at UNESA. The collected data were analyzed using a paired sample test, and the results of the study indicate a significant impact of implementing instructional video media on students' skills in developing storyboards.